Genetic and environmental variation in reproductive and lactational performance of Jersey cattle in the coastal lowland semi-humid tropics - Njubi, D.M.; Rege, J.E.O.; Thorpe, W.R.; Collins-Lusweti, E.; Nyambaka, R. (Springer, 1992)
Evaluates the reproductive and lactational performances, length of productive life of the Jersey breed from records for 1960 to 1988 in coastal lowland semi-humid Kenya. Reports estimates of reproductive and lactational performance, the effects of non-genetic factors on performance and estimates of genetic parameters for various performance traits. Reports also the phenotypic and genetic trends for milk yield and calving interval in the herd. Table I gives the mean performance for the study period. The results showed that on average the Jersey calved first after conceiving at about 22 months of age, produced nearly 1,800 kg milk/lactation and remained in the herd for 3.3 lactations. The mean calving interval of 408 days resulted in a production of about 1,670 kg milk/cow/year during a productive life of 36 months. Table II gives statistical significance of the systematic environmental effects in the analysis of variance of the reproductive and lactation traits. Estimates of repeatabilities, phenotypic and genetic correlation are presented in table II. Figure 1 & 2 shows clearly that the decline in both lactational and reproductive performances resulted not from genetic but environmental deterioration.